Abnormal Ferroptosis in Myelodysplastic Syndrome - Lv, Qi; Niu, Haiyue; Yue, Lanzhu; Liu, Jiaxi; Yang, Liyan; Liu, Chunyan; Jiang, Huijuan; Dong, Shuwen; Shao, Zonghong; Xing, Limin; Wang, Huaquan (Frontiers in Oncology, 2020)
BACKGROUND: Ferroptosis is a form of iron-dependent non-apoptotic cell death, with characteristics of loss of the activity of the lipid repair enzyme, glutathione peroxidase 4 (GPX4), and accumulation of lethal reactive lipid oxygen species. The mechanism of ferroptosis in MDS is unclear. METHODS: Cell viability assay, reactive oxygen species (ROS) assay, glutathione assay, glutathione peroxidase activity assay were performed to study the regulation of ferroptosis in MDS cells obtained from MDS patients, the iron overload model mice and cell lines. RESULTS: The growth-inhibitory effect of decitabine could be partially reversed by ferrostatin-1 and iron chelating agent (DFO) in MDS cell lines. Erastin could increase the cytotoxicity of decitabine on MDS cells. The level of GSH and the activity of GPX4 decreased while the ROS level increased in MDS cells upon treatment with decitabine, which could be reversed by ferrostatin-1. The concentration of hemoglobin in peripheral blood of iron overload mice was negatively correlated with intracellular Fe2+ level and ferritin concentration. Iron overload (IO) led to decreased viability of bone marrow mononuclear cells (BMMNCs), which was negatively correlated with intracellular Fe2+ level. Ferrostatin-1 partially reversed the decline of cell viability in IO groups. The level of GSH and the activity of GPX4 decreased while the ROS level increased in BMMNCs of IO mice. DFO could increase the level of GSH. Ferrostatin-1 and DFO could increase the GPX4 activity of BMMNCs in IO mice. Ferrostatin-1 could significantly reverse the growth-inhibitory effect of decitabine in MDS patients. Decitabine could significantly increase the ROS level in MDS groups, which could be inhibited by ferrostatin-1 or promoted by erastin. Ferrostatin-1 could significantly reverse the inhibitory effect of decitabine on GSH level in MDS patients. Erastin combined with decitabine could further reduce the GSH level. Erastin could further decrease the activity of GPX4 compared with decitabine group. CONCLUSIONS: Ferroptosis may account for the main mechanisms of how decitabine induced death of MDS cells. Decitabine-induced ROS raise leads to ferroptosis in MDS cells by decreasing GSH level and GPX4 activity.